1972
DOI: 10.1016/0017-9310(72)90237-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer to the transpired turbulent boundary layer

Abstract: This paper contains a summarization of five years work on an investigation on heat transfer to the transpired turbulent boundary layer, The experimental results are presented for friction coefficient and Stanton number over a wide range of blowing and suction for the case of constant free-stream velocFty, 5olding ccnstarrt certain blowing parameters. The problem of the accelerated turbulent boundary layer with transpiration is considered, experimental data are presented and discussed, and theoretical models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 8 publications
(3 reference statements)
1
39
0
Order By: Relevance
“…The response of smooth wal l boundary layers to acceleration is discussed in the suninary report by Kays and Moffat [4]. Briefly, smooth wall layer dIJ 0, accelera ti ons are charac ter i zed by the acce l era tion param eter , K = -~~~~ -s--.…”
Section: /6 2 'mentioning
confidence: 99%
“…The response of smooth wal l boundary layers to acceleration is discussed in the suninary report by Kays and Moffat [4]. Briefly, smooth wall layer dIJ 0, accelera ti ons are charac ter i zed by the acce l era tion param eter , K = -~~~~ -s--.…”
Section: /6 2 'mentioning
confidence: 99%
“…This work showed also that the theory of Rubesin cannot be applied for high blowing ratios, at which a homogenous gas injection through the porous material is violated. Further similar fundamental studies on transpiration cooling showed the big potential of this technique for its application on turbine blades and combustion chambers (Luikov 1963;Kays 1972). The capabilities could significantly be extended with porous ceramic composite materials (CMC).…”
Section: Introductionmentioning
confidence: 99%
“…0 Kays [1972] shows that transpired turbulent boundary layers seem to respond to local conditions. That is a boundary layer experiencing a sudden change in injection will, following a short period of adjustment, behave as though it had always been subject to that level of injection.…”
mentioning
confidence: 99%